Economic aspects of pharmacotherapy of servicemen with injury and wound of the brain - A. P. Shmatenko; Yu. V. Rumyancev; O. M. Vlasenko; O. V. Pleshkova (The State Expert Center of the Ministry of Health of Ukraine, 2018)
The fighting in the area of the antiterrorist operation led to a large number of injuries among servicemen who are serving in the east of the country. Injuries and wound of the brain occupy about 35-40% among the total level of injury. and mortality in severe traumatic brain injury is 70%. All this has determined the relevance of the study of medical treatment of servicemen with injury and wound of the brain., Numerous pharmacotherapeutic schemes have been proposed for the treatment of victims with this pathology, aimed at preventing brain hypoxia, improving metabolic processes, normalizing life support functions and intracranial pressure, and the price range of pharmacotherapy of this pathology varies considerably, that's why the aim of our work is to establish the cost indicators of the main directions of pharmacotherapy of affected servicemen with injury and wound of the brain.The main directions of the pharmacotherapy of injuries and wounds of the brain have been identified as a result of the analysis of the scientific literature and primary medical documentation, which include: normalization of life-supporting functions and brain metabolism; treatment of intracranial hypertension; restoration of microcirculation and cerebral circulation; elimination of excitation and convulsions; antibacterial, analgesic, anti-inflammatory, blood-resuscitating and symptomatic therapy. Analysis of the dependence of the cost of treatment on the severity of the affected servicemen with injury and wound of the brain showed that the most expensive is the pharmacotherapy of severe injuries and wounds, the average cost of treatment of the affected is 139,98 UAH for 1 patient per day. The average cost of medicines for the treatment of servicemen with injuries and wounds of medium and mild severity was 67,23 and 42,26 UAH per day respectively We analyzed the total costs spent on these directions of pharmacotherapy and found that the greatest cost is characterized by the costs of normalizing brain metabolism, the costs are 1 261,21 UAH per patient, this accounts for 38% of the total cost of medicines. Also, the most expensive directions are antibacterial - 649,27 UAH (19%) and analgesic therapy - 375,90 UAH (11%). The least expenses are expended on anti-inflammatory therapy, the cost of which is 19,96 UAH. Analyzing the daily cost of one day of treatment of affected it was found that the most expensive are the first 7 days of treatment.